Pathological and clinical study of calcification of the mitral valve ring - Pomerance, Ariela (1970)
The pathology and clinical features of 258 cases of mitral ring calcification were reviewed. The overall incidence in patients over 50 years of age was 8·5%; it was more than twice as high in women (11·5%) as in men (4·5%) and rose sharply with age. Cardiac failure and systolic murmurs were each noted in over half the patients. Hypertension was slightly commoner than in age- and sex-matched groups without ring calcification, although the difference was not statistically significant. Small nodules of calcification were more frequent in men and heavy deposits in women. Distortion and atrial displacement of the posterior mitral cusp was present in 26% of the hearts with early ring calcification, in 56% of the hearts with moderate, and in almost all hearts with marked changes. Systolic murmurs had been heard in 73% of these cases. `Caseation' of the calcified ring was seen in seven hearts and haemorrhagic valvulitis in three. Calcium had ulcerated through the cusp in 12 cases, with thrombotic and/or bacterial endocarditis in five. Aortic valve calcification was present in 36% of men and was quantitatively related to the severity of mitral ring calcification. In women the incidence was 30% and there was no corresponding quantitative relationship. Microscopy showed nonspecific chronic inflammatory changes adjacent to calcium in about half the cases in both sexes, with foreign body type giant cells in 6%. Similar inflammatory changes in the valve cusp were almost twice as common in women as in men. There was no evidence that previous endocarditis was responsible for mitral ring calcification, neither did parity influence its incidence. Severe coronary atherosclerosis was unrelated but severe aortic atherosclerosis was commoner in patients with calcified mitral rings. The difference, in women, was statistically significant. The higher incidence of severe degrees of ring calcification, complications, and valvular inflammation in women suggests a sex-determined difference in tissue response in the mitral area. Possible provoking factors apply to both sexes and both left side valves, and such a difference would account for the relative frequency and sex incidence of mitral ring calcification.